Narrative inquiry and the search for connectedness: practitioners and academics developing public administration scholar - Ospina, Sonia M.; Dodge, Jennifer (2005)
Maintaining a vibrant field of public administration requires ongoing efforts to link the world of academic researchers and practitioners. We suggest that research itself, traditionally pursued by academics, is a promising mechanism for making this connection. In particular, researchers and practitioners in public administration can do research together in a way that enhances mutual learning, draws on the strengthes of each to create useful knowledge of high quality, appreciates and tolerates of each others' worlds, styles, and contributions. Using research to promote connectedness means rethinking the roles that practitioners and academics play in generating knowledge in the field. In our project, insights from the assumptions and practices of narrative inquiry helped us to identify three research roles for practitioners: as sources of knowledge, as producers of knowledge, and as active consumers who inform the research process. - Reproduced.
Keywords: Public administration